2023
DOI: 10.3390/nu15020350
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Potentials of Taxifolin for Obesity-Induced Hepatic Steatosis, Fibrogenesis, and Tumorigenesis

Abstract: The molecular pathogenesis of nonalcoholic steatohepatitis (NASH) includes a complex interaction of metabolic stress and inflammatory stimuli. Considering the therapeutic goals of NASH, it is important to determine whether the treatment can prevent the progression from NASH to hepatocellular carcinoma. Taxifolin, also known as dihydroquercetin, is a natural bioactive flavonoid with antioxidant and anti-inflammatory properties commonly found in various foods and health supplement products. In this study, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this study, 13 components of TF were identified by UHPLC-QTOF-MS. Dihydromyricetin, myricetin, and myricitrin are found to be the most abundant and bioactive flavonoids in Vine tea, which have ameliorative effect on NAFLD (Zhang et al, 2021). In addition, epigallocatechin, taxifolin, and hesperidin have ameliorative effects on NAFLD (Ding et al, 2023;Inoue et al, 2023;Li et al, 2022). To investigate whether flavonoids extracted from vine tea have an ameliorative effect on NAFLD, we administered TF through gavage in mice fed the HFD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 13 components of TF were identified by UHPLC-QTOF-MS. Dihydromyricetin, myricetin, and myricitrin are found to be the most abundant and bioactive flavonoids in Vine tea, which have ameliorative effect on NAFLD (Zhang et al, 2021). In addition, epigallocatechin, taxifolin, and hesperidin have ameliorative effects on NAFLD (Ding et al, 2023;Inoue et al, 2023;Li et al, 2022). To investigate whether flavonoids extracted from vine tea have an ameliorative effect on NAFLD, we administered TF through gavage in mice fed the HFD.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and radical scavenging activities of taxifolin reduced HG-induced ROS production, which further suppressed the TXNIP–NLRP3 axis, thereby inhibiting IL-1β production. Since taxifolin also has beneficial effects on glucose metabolism under diabetic conditions [ 30 ], it can indirectly suppress cognitive impairment by improving metabolism; therefore, the indirect effects and direct impact of taxifolin on the microglia can synergistically prevent and/or improve diabetes-related cognitive impairment. Future preclinical and clinical studies to address the in vivo effects of taxifolin on neuroinflammation in diabetic conditions would be helpful in developing novel strategies to prevent diabetes-related cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that orally administered taxifolin improves cerebral blood flow, promotes amyloid-β removal from the brain, and prevents cognitive decline [ 28 ]; it also demonstrated suppressive effects on neuroinflammation [ 29 ] in a mouse model of cerebral amyloid angiopathy. We further demonstrated the beneficial effects of taxifolin on the metabolism of obesogenic diet-fed mice; taxifolin improved glucose/lipid metabolism, obesity, and hepatic steatosis, thereby preventing nonalcoholic steatohepatitis [ 30 ]. Moreover, we recently revealed that the oral intake of taxifolin exhibits beneficial effects on the cognitive function in patients with mild cognitive impairment or mild dementia [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, taxifolin displays pleiotropic effects for the treatment of the NASH continuum. It could alleviate obesity-induced hepatic steatosis, fibrosis, and tumorigenesis in rodent models (63). Sitagliptin is a selective inhibitor of dipeptidyl peptidase-4 (DPP-4I), which is widely used as a hypoglycemic agent.…”
Section: Discussionmentioning
confidence: 99%